2012
DOI: 10.1111/j.1939-1676.2012.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

BartonellaSpecies Antibodies and Hyperglobulinemia in Privately Owned Cats

Abstract: Background Bartonella species are zoonotic agents and primary pathogens in cats. Hyperglobulinemia has been associated with bartonellosis in humans and cats. Hypothesis/Objectives To evaluate for associations between Bartonella species immunoglobulin G (IgG) antibodies and serum biochemistry panel results in privately owned cats. Animals 1,477 privately owned cats. Methods Residual sera were collected after biochemical evaluation for this prospective, cross‐sectional serosurvey. Bartonella species IgG ELISA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…Hematological findings in Bartonella spp. infected cats are uncommon [9][10][11], although anemia, neutropenia and eosinophilia have been described in experimental infections [9,10]. Lymphocythosis has been strongly associated with the presence of B. henselae antibodies among naturally infected cats, probably due to induced polyclonal gammopathy [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematological findings in Bartonella spp. infected cats are uncommon [9][10][11], although anemia, neutropenia and eosinophilia have been described in experimental infections [9,10]. Lymphocythosis has been strongly associated with the presence of B. henselae antibodies among naturally infected cats, probably due to induced polyclonal gammopathy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies have not proven an association between Bartonella and anemia, gingivostomatitis, neurologic conditions or uveitis [7,8]. Fever, lethargy, anorexia, local lymphadenopathy, myocarditis, neurologic disorders, among others, have been observed in experimental infections [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…antibodies have correlated with polyclonal hyperglobulinaemia and hypoglycaemia. 50 Hyperinsulinemic hypoglycaemia syndrome has been reported in two dogs infected with a Bartonella sp. 51 Monoclonal gammopathies have been reported in association with bartonellosis in cats, dogs and humans.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…[16][17][18][19][20][21] However, Whittemore et al found a correlation between Bartonella species antibodies and hypergammaglobulinemia in cats. 22 Sykes et al found an association between gingivitis and stomatitis and culturing Bartonella species from bacteremic cats, whereas there was no statistical difference in seroprevalence between cases and controls. 21 Also, a study from Switzerland, where the overall B henselae seroprevalence in 728 cats was low (8.3%) compared with many regions in North America where cat population seroprevalences are >40%, found a statistical correlation between seroreactivity and stomatitis.…”
Section: Discussionmentioning
confidence: 99%